FAKTOR- FAKTOR PRILAKU PEMELIHARAAN KESEHATAN GIGI SISWA SEKOLAH DASAR TERHADAP KEJADIAN KARIES GIGI - NINING NINGRUM; Eliza Herijulianti; Tiurmina Sirait (Poltekkes Kemenkes Bandung, 2022)
Most often dental and oral health experienced by school-age children is caries. Reason behind dental caries mostly by bad habits, lack of awareness to treat dental and oral hygiene lead micro-organisms in plaque continue spread on the surface of the teeth cause plaque gets thicker, beside the habit not taking care it, children have habit od eating sweet foods, contain simple sugars, the purpose knowing the behavioral factors in dental health maintenance elementary school studentstowards caries at SDN Ciptakarya Baleendah Bandung Regency. The type of research was cross-sectional, number of samples was all students in grades 4,5,6 SD Cipta Karya Baleendah Bandung Regency, methodwas proportional random sampling sample with results96people. Connection between dental health maintenance behavior and incidence of caries was carried out by bivariate test between independent variables on the dependent variable using Chi Square test. The results of Univariate test, students at SDN Ciptakarya Baleendah, Bandung Regency, most of them had caries 59%, teeth brushing habits were quite good 65%, eating habits - cariogenic foods were not good 55.57%, eating habits - non-cariogenic foods 83%, gargling after snacks less both 96.0% and control to the dental clinic 52%. The results of the bivariate test of dental and oral health maintenance behavior showed that gargling after eating had a relationship with caries, namely p = 0.039 ( p < 0.05).